Evaluation of Aromatic hydrocarbons ( PHAs) in some drinking water wells in Baghdad - Ali, Abduljabbar A.; Al-paruany, Kamal B.; Alazawi, Ansam S. (Iraqi Journal of Science, 2025)
Polycyclic Aromatic Hydrocarbons (PAHs), which are chemical molecules, have been causing numerous health and environmental issues in water supplies. This study investigated the levels of PAHs in groundwater samples collected from the Diyala Bridge and Al-Ahdamiyah districts between March and June 2023. Ten groundwater samples were collected from different locations; six wells were distributed in the Diyala Bridge area and four in the Adhamiya area. The results show that the average total amounts of PAHs in each water sample in Diyala Bridge and Al-Ahdamiyah districts ranged between 16.0 – 472.63 ppm with a mean of 213.13ppm, which is significantly higher than the ten ppm control. During the study period, Several locations reported noticeably elevated concentrations of one or both of the chosen PAHs. The highest concentration of PAHs was recorded for the chrysene compound at the Abu-Hassan site of 284ppm, followed by pyrene and acenophthylene, with a concentration of 167.8 and 131.7ppm, respectively. The lowest concentrations were for Naphthalene, which were 0.0213 and 0.041 in Qassim and Abu-Hassan wells, respectively. It also noted that high concentrations were recorded for all PAHs at the Mohammed, Ahmad, and Qassim wells, which exceeded significantly for other sites. This research advice focuses more on the risk evaluation of PAHs for well water sources when used for drinking.